2006
DOI: 10.1074/jbc.m609384200
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanism for the Heparan Sulfate Dependence of Slit-Robo Signaling

Abstract: Slit is a large secreted protein that provides important guidance cues in the developing nervous system and in other organs. Signaling by Slit requires two receptors, Robo transmembrane proteins and heparan sulfate (HS) proteoglycans. How HS controls Slit-Robo signaling is unclear. Here we show that the second leucine-rich repeat domain (D2) of Slit, which mediates binding to Robo receptors, also contains a functionally important binding site for heparin, a highly sulfated variant of HS. Heparin markedly enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(135 citation statements)
references
References 31 publications
8
127
0
Order By: Relevance
“…11 A-F Mechanistically, Hsts might exert their influence on Robo/Slit signaling biochemically by regulating the formation of the Robo/ Slit/HS signaling complex (Hussain et al, 2006), the distribution of Slit proteins (Johnson et al, 2004), or gene expression. HSPGs modulate the activity of morphogens, including Wnt, Shh and FGF, which control gene expression (Perrimon and Bernfield, 2000;Selleck, 2000;Lin, 2004 Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A-F Mechanistically, Hsts might exert their influence on Robo/Slit signaling biochemically by regulating the formation of the Robo/ Slit/HS signaling complex (Hussain et al, 2006), the distribution of Slit proteins (Johnson et al, 2004), or gene expression. HSPGs modulate the activity of morphogens, including Wnt, Shh and FGF, which control gene expression (Perrimon and Bernfield, 2000;Selleck, 2000;Lin, 2004 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…HSPGs are cofactors in the cellular response to secreted proteins, including Slits and FGFs (supplemental Fig. 1 A, available at www.jneurosci.org as supplemental material), involved in the development of axon pathways so HS could play a pivotal coordinating role (Dickson, 2002;Inatani et al, 2003;Johnson et al, 2004;Kantor et al, 2004;Lee and Chien, 2004;Lin, 2004;Hussain et al, 2006;Sánchez-Camacho and Bovolenta, 2009). HS is critically important for corpus callosum and optic chiasm development as both develop abnormally when HS biosynthesis is blocked in the developing mouse embryonic brain (Inatani et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these examinations showed that Slit3 interacts with both Robo1 and Robo4, confirming and also extending previous findings. 20,39,40 To test whether the Slit3-Robo interaction modulates EC function, we applied the Slit3-induced EC chemotaxis assay as the readout. The functional blocking anti-Robo1, anti-Robo4 (supplemental Figure 3C-D), or nonimmune antibody from the same animal species was supplemented into the Slit3-or VEGFcontaining bottom chambers of the assay.…”
Section: Slit3 Interacts With Robo4 To Mediate Endothelial Chemoattramentioning
confidence: 99%
“…Eighty nanograms of concentrated Slit2-Myc polypeptide were used in combination with 20 ng of HGF. Always, soluble Slit 2-Myc polypeptide was administrated together with heparin, as described previously (Hussain et al, 2006). Transwell migration and tubulogenesis assays were performed and quantified as described previously (Stella et al, 2005).…”
Section: Biological Assaysmentioning
confidence: 99%